Benchmark problems for contact dynamics in multibody systems - Masoudi, Ramin (2014)
Principles of contact mechanics and contact dynamics dates back to the 1800s, when Heinrich Hertz published his pioneering works On Contact Between Elastic Bodies [3] and Miscellaneous Papers [4], with a broad application in engineering sciences such as robotics, vehicle and train dynamics, biomechanics, and aerospace engineering. Of course, outstanding works by Sir Isaac Newton on impact dynamics between two rigid bodies have been one of the leading attempts to mathematically formulate the mechanical interaction between two colliding bodies. In recent decades, the value of contact dynamics has been more essential in math-based modeling of multibody systems, as multibody dynamics is further involved in realistic modeling of a wide range of various physical systems.